Implementación de un sistema electrónico para la medición de variables de cuencas hidrográficas mediante la utilización de un dron en la provincia de Cotopaxi - Constante Cruz, Freddy Rolando (2020)
This present project allows to capture the investigation in the design and implementation of the electronic system for the taking of methodological variables of watersheds by using a drone due to the traditional method is done by manually way and using several equipments that causes disadvantages in function of time and discomfort at the time of study. The implementation has as purpose the accuracy on necessary stock taking for the user and time optimization in the taking of meteorological data of the area. The compilation of categorized information will depend of the good selection of electronic elements, circuitry development and programming for the optimal configuration of electronic system. On the other hand, the drone will be used as a means of transportation of electronic system that will be in charge of data taking, achieving to perform a comfortably job on lands with difficult access, with certain level of danger and at different altitude. The electronic system is conformed with power source, smart micro controller for the taking and information storage for category, meassure variable and altitude. This implementation aims to improve the field study for subsequent investigations, reduction of time and costs of a certain place where it is needed to get meteorological variables with higher degree of accuracy according to the height.